Playing tactics, contextual variables and offensive effectiveness in English Premier League soccer matches. A multilevel analysis - González-Rodenas, J.; Aranda-Malaves, R.; Tudela-Desantes, A.; Nieto, F.; Usó, F.; Aranda, R. (PLOS ONE, 2020)
The aim of this study was to investigate the combined effects of tactical and contextual indicators on achieving offensive penetration and scoring opportunities in English Premier League (EPL) soccer matches. A total of 1971 team possessions from 20 random matches were evaluated by means of multidimensional observation. The EPL matches had a great proportion of fast attacks (36.0%) followed by combinative (29.6%), direct attacks (24.1%) and counterattacks (9.5%). Multilevel logistic regression models revealed that counterattacks (OR = 3.428; 95% CI: 2.004-5.864; P<0.001) were more effective to create goal scoring opportunities than combinative attacks, while direct attacks showed to be less effective (OR = 0.472; 95% CI: 0.264-0.845; P<0.05). Playing at home increased the probability (OR = 1.530; 95% CI: 1.097-2.135; P<0.05) of creating goal scoring opportunities compared with playing away. These findings show the multifactorial character of soccer and how different contextual and tactical indicators can influence the creation of offensive penetration and goal scoring opportunities in the English Premier League.